Study on the Mechanism of Failure in the LiF–NaF–KF Molten-Salt-Purifying Processing System - Liu, Huajian; Chen, Shuangjian; Fu, Jie; Yang, Xinmei; Tang, Rui; Ge, Min; Wang, Jianqiang; Zhou, Xingtai; Xie, Leidong (Frontiers in Materials, 2022)
The failure of LiF–NaF–KF molten salt processing engineering was investigated. Results indicate that the failure is related to the blockage of pipes. The mechanism of blockage was studied systemically and results reveal that the blockages of pipes were attributed to the corrosion. Ni201 vessel was corroded in molten salt to form KNiF3 and K2NiF4. Corrosion products were reduced by H2 to form metallic Ni which is precipitant in salt. The transfer of precipitant in terminal salt was stopped by the incomplete root penetration, which results in one pipe blocked at the welded joint. Corrosion products were reduced by H2 to form metallic Ni and deposited on the inner surface of H2 gas outlet, which results in another pipe blocked.